Beneficial effect of standardized extracts of Amorphophallus paeoniifolius tuber and its active constituents on experimental constipation in rats. Issue 5 (May 2020) - Dey, Yadu Nandan; Wanjari, Manish M.; Srivastava, Bhavana; Kumar, Dharmendra; Sharma, Deepti; Sharma, Jyoti; Gaidhani, Sudesh
Abstract: The tubers of Amorphophallus paeoniifolius (Elephant foot yam), principally consumed as crop food and vegetables, are used in ethno-medicinal practices in mitigation of constipation and piles. Hence, present study evaluated the effect of tubers of A. paeoniifolius and its active constituents glucomannan and betulinic acid on experimentally-induced constipation. The tuber and its extracts were standardized as per Ayurvedic Pharmacopoeia of India and physicochemical constants were found within the pharmacopoeial limit. HPTLC fingerprint profile of extracts has been developed using suitable mobile phase. Methanolic extract was subjected to column chromatography. The isolated phytoconstituents were characterized by FT-IR, NMR and MS and identified as betulinic acid and β-sitosterol. Functional constipation was induced in rats by oral administration of loperamide (3 mg/kg) for first 3 consecutive days. The rats were orally treated with methanolic and aqueous tuber extracts in the doses of 125, 250 and 500 mg/kg, glucomannan (300 mg/kg) and betulinic acid (1.5 mg/kg) for 7 days. The parameters viz. number of stools, wet weight of stools and moisture content of stools and intestinal transit were studied. Treatment with tuber extracts, glucomannan and betulinic acid showed significant ( p < 0.05) increase in fecal parameters and intestinal transit in constipated rats. The effects were comparable to standard laxative drug, sodium picosulfate (5 mg/kg, orally). The results indicated that tuber extracts and its active constituents showed laxative effect and relieved constipation. It is concluded that tuber of A. paeoniifolius exhibited beneficial effect in functional constipation possibly through its laxative action. The study validates its ethno-medicinal use in correction of constipation. The principal constituents, betulinic acid and glucomannan in tuber extracts might have played important role in relieving the constipation. Abstract : Food Science; Pharmaceutical science; Loperamide; Rats; Constipation; Glucomannan; Betulinic acid; HPTLC